Highly Hydrophilic Polyurethane Foam Dressing Versus Early Hydrophilic Polyurethane Foam Dressing on Skin Graft Donor Site Healing in Patients with Diabetes: An Exploratory Clinical Trial. (June 2020) - Namgoong, Sik; Jung, Jae-Eun; Yoon, Young-Don; Han, Seung-Kyu; Lee, Ye-Na; Son, Ji-Won
ABSTRACT: OBJECTIVE: To compare the effects of early hydrophilic polyurethane (EHP) foam dressing and highly hydrophilic polyurethane (HHP) foam dressing on wound healing in patients with diabetes. METHODS: Twenty patients with diabetes with skin graft donor sites on the lateral thigh were enrolled in this study. Each donor site was divided into two equal-sized areas for the application of HHP or EHP foam dressing. The study endpoint was the time required for healing, defined as complete epithelialization of the donor site without discharge. All possible adverse events were also documented. MAIN RESULTS: Donor site healing was faster in 15 patients on the HHP half and 1 patient on the EHP half. In four patients, healing rates were the same between the HHP and EHP areas. Donor sites treated with HHP and EHP foam dressings healed in 17.2 ± 4.4 and 19.6 ± 3.7 days ( P = .007), respectively. During the study period, no adverse event associated with the dressings occurred in either group. CONCLUSIONS: The HHP foam dressing might provide faster healing than EHP foam dressing for skin graft donor sites in patients with diabetes.